2008
DOI: 10.1161/circep.107.750471
|View full text |Cite
|
Sign up to set email alerts
|

Altered Sympathetic Nervous Reactivity and Norepinephrine Transporter Expression in Patients With Postural Tachycardia Syndrome

Abstract: Background-Clinical observations in patients with postural tachycardia syndrome (POTS) suggest abnormal sympathetic nervous system activity and a dysfunction of the norepinephrine (NE) transporter (NET). Methods and Results-We examined sympathetic nervous system responses to head-up tilt by combining NE plasma kinetics measurements and muscle sympathetic nerve activity recordings and by quantifying NET protein content in peripheral sympathetic nerves in patients with POTS compared with that in controls. POTS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 32 publications
1
55
1
Order By: Relevance
“…It is likely that the association between depression and cognitive performance reflects the underlying neurobiology of depression, with alterations in brain monoamines influencing both depression and cognition (Lambert et al, 2000; Austin et al, 2001; Schmitt et al, 2006; Barton et al, 2008; Wingen et al, 2008; Chalermpalanupap et al, 2013). Noradrenaline transporter (NET) dysfunction is evident in patients with POTS (Shannon et al, 2000; Lambert et al, 2008) and in untreated patients with major depressive disorder (Barton et al, 2007). Interestingly, genetic variation in the NET gene has been associated with deficits in memory and attention in patients with ADHD (Thakur et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the association between depression and cognitive performance reflects the underlying neurobiology of depression, with alterations in brain monoamines influencing both depression and cognition (Lambert et al, 2000; Austin et al, 2001; Schmitt et al, 2006; Barton et al, 2008; Wingen et al, 2008; Chalermpalanupap et al, 2013). Noradrenaline transporter (NET) dysfunction is evident in patients with POTS (Shannon et al, 2000; Lambert et al, 2008) and in untreated patients with major depressive disorder (Barton et al, 2007). Interestingly, genetic variation in the NET gene has been associated with deficits in memory and attention in patients with ADHD (Thakur et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…More robust and precise assessment of sympathetic activity by direct measurements of total body and regional noradrenaline spillover have been performed in a few investigations and the results have been variable. Evidence of sympathoexitation was confirmed in one study (Jordan et al, 2002), but not in others (Jacob et al, 1999; Goldstein et al, 2002a; Lambert et al, 2008). The possible hyperadrenergic features of POTS may not be simply due to increased central sympathetic outflow and noradrenaline release but potentially from an augmentation of the sympathetic signal due to enhanced receptor sensitivity or to a reduction in noradrenaline clearance during standing.…”
Section: Sympathetic Overactivity May Be Associated With Potsmentioning
confidence: 93%
“…Some investigations (Streeten et al, 1988; Schondorf and Low, 1993; Furlan et al, 1998; Jacob et al, 1999), but not all (Jacob et al, 2000; Lambert et al, 2008), have reported that POTS patients have greater systemic plasma noradrenaline concentrations at rest or during orthostasis compared with healthy controls, suggesting that POTS is associated with a hyperadrenergic state. More robust and precise assessment of sympathetic activity by direct measurements of total body and regional noradrenaline spillover have been performed in a few investigations and the results have been variable.…”
Section: Sympathetic Overactivity May Be Associated With Potsmentioning
confidence: 99%
“…Impaired neuronal noradrenaline reuptake, as a solitary identified abnormality in patients with the postural tachycardia syndrome, 70,82 is not associated with heart disease or reduced longevity. Conversely, with the coexistence of impaired norepinephrine reuptake with firing salvos in normal-weight essential hypertension 31,[33][34][35][36] and in depressive illness 42,51,79 and panic disorder, 51,79,80 there is evidence of cardiac risk, 84 even in panic disorder.…”
Section: Sympathetic Nerve Adrenaline Cotransmissionmentioning
confidence: 99%